OSESIMMETRIK JISMLARDA NOSTATSIONAR ISSIQLIK TARQALISH MASALASINI CHEKLI ELEMENTLAR USULIDA SONLI MODELLASHTIRISH - Sapayev, Sh.O. (SCIENCE and SOCIETY, 2025)
In the article, based on FEM, a numerical model for solving non-stationary problems of heat dissipation in axisymmetric bodies is developed, and an algorithm and software for solving the problem are created.
Keywords: axisymmetric; non-stationary; cylindrical coordinates; discrete model; temperature